Snapdragon (Antirrhinum majus L.): a retrospective review of contemporary breeding - I. V. Barabanov; M. V. Vasilieva; I. N. Anisimova; R. S. Rakhmangulov (Труды по прикладной ботанике, генетике и селекции, 2025)
Today, studying molecular genetic bases of important agronomic traits and mechanisms of intervarietal and interspecific differences is of considerable interest for ornamental crop breeding. General characteristics and advantages of snapdragon (Antirrhinum majus) as a model object for genetic research are presented. Main blocks of genes encoding plant characters that ensure the ornamental value (flower and inflorescence shapes, corolla color, etc.) are discussed. Considerable attention is paid to the activity of mobile elements, and transposon-associated mutagenesis.